Pengaruh Penggunaan Media Pembelajaran Assemblr EDU Terhadap Motivasi dan Hasil Belajar Siswa Pada Materi ASEAN Kelas VI - Sofyan Iskandar; Primanita Sholihah Rosmana; Eka Ariya Mutiara; Farras Adzra Nisrina; Nesty Ermin Nadhirah; Nurfenti Widya Nengsih (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2022)
The use of digital technology-based learning media is certainly an important thing to do at this time. Therefore, more and more digital learning media are developing on the internet today, one of which is Assemblr EDU. Assemblr EDU is a 3D-based digital learning platform that can be used as a medium for providing materials, questions and various other important educational information. The purpose of this study was to see the level of enthusiasm for learning children and learning achievement when using Assemblr media as a learning support. The research method used is quantitative, which requires observations involving many observed objects to find accurate data. . The results obtained after using Assemblr in learning, the enthusiasm of students is increasing which of course affects the increase in children's learning achievement. There is an increase in the assessment carried out after the learning activities have ended which of course this shows that the use of Assemblr EDU digital learning media is suitable for implementation to elementary school students grade VI. Keywords: Assemblr; Student; Enhancement; Theory